Model Development of Training Management for Maritime Transport Apparatus at Amurang Sea Port: A Qualitative Study on Planning, Implementation, Evaluation, and Career-Linked Improvement - Moh. Qowi; Jeffry Sony Junus Lengkong; Joulanda A M Rawis; Henny Nikolin Tambingon; Ruth Umbase (International Journal of Information Technology and Education, 2025)
This study develops and analyzes a Training Management Model for maritime transport apparatus serving at Amurang Sea Port, focusing on how training is planned, implemented, evaluated, and redesigned into a more contextual and career-linked system. The research problem emerges from the persistent gap between training programs administered through BP2TL (Balai Pendidikan dan Pelatihan Transportasi Laut) and the real operational needs of small ports, where limited infrastructure, constrained budgets, and bureaucratic routines often reduce training relevance and post-training application. The study employs a qualitative descriptive approach, using in-depth interviews, observation, and document analysis to capture the practices and constraints across training management stages. Findings show that training planning has followed formal guidance and standards; however, it remains dominated by administrative routines and has not fully adopted a dynamic, field-driven training needs assessment. Key planning gaps include limited flexibility of training budgets, weak integration between training and career pathways, insufficient contextualization of training modules for small-port operations, and minimal utilization of evaluation outputs for subsequent planning cycles. Implementation is delivered through formal mechanisms but is not yet optimal: training methods are still heavily theoretical (lecture-based), simulation and case-based practice remain limited, and schedules often conflict with participants’ operational duties, restricting participation and learning transfer. Evaluation tends to emphasize administrative outputs (attendance and certification) rather than measuring competence, behavioral change, and work-unit performance impacts. Based on these findings, the study proposes a revised model that is contextual, decentralized, and unit-needs-based, integrating comprehensive evaluation frameworks (ADDIE, Kirkpatrick, and CIPP) to treat the port environment as a “real learning laboratory” and participants as change agents. The study concludes that shifting training management from annual compliance routines to an outcome-oriented human resource development strategy is essential for strengthening safety, service quality, and professionalism in maritime public services at small ports.